Pre-symbiotic response of the compatible host spruce and low-compatibility host pine to the ectomycorrhizal fungus Tricholoma vaccinum - Ezediokpu, Marycolette Ndidi; Halitschke, Rayko; Krause, Katrin; Boland, Wilhelm; Kothe, Erika (Frontiers in Microbiology, 2023)
Mutualistic ectomycorrhizal symbiosis requires the exchange of signals even before direct contact of the partners. Volatiles, and specifically volatile terpenoids, can be detected at a distance and may trigger downstream signaling and reprogramming of metabolic responses. The late-stage ectomycorrhizal fungus Tricholoma vaccinum shows high host specificity with its main host spruce, Picea abies, while rarely associations can be found with pine, Pinus sylvestris. Hence, a comparison of the host and the low-compatibility host’s responses can untangle differences in early signaling during mycorrhiza formation. We investigated sesquiterpenes and identified different patterns of phytohormone responses with spruce and pine. To test the specific role of volatiles, trees were exposed to the complete volatilome of the fungus versus volatiles present when terpene synthases were inhibited by rosuvastatin. The pleiotropic response in spruce included three non-identified products, a pyridine derivative as well as two diterpenes. In pine, other terpenoids responded to the fungal signal. Using exposure to the fungal volatilome with or without terpene synthesis inhibited, we could find a molecular explanation for the longer time needed to establish the low-compatibility interaction.